Evaluating the diversity and composition of bacterial communities associated with Acacia gerrardii - the only existing native tree species in Kuwait desert. - Suleiman, M.; Dixon, Kingsley; Commander, L.; Nevill, Paul; Quoreshi, A.; Bhat, N.; Manuvel, A.; Sivadasan, M. (2018)
We investigated the diversity and composition of bacterial communities in rhizospheric and non-rhizospheric bulk soils as well as root nodule bacterial communities of Acacia gerrardii - the only native tree species existing in the Kuwait desert. Community fingerprinting comparisons and 16S rDNA sequence identifications were used for characterization of the bacterial population using specific primers. The bacterial characterization of soil samples revealed four major phyla, namely: Acidobacteria, Bacteroidetes, Firmicutes and Proteobacteria. In-situ (Desert) samples of both rhizospheric and non-rhizospheric bulk soil were dominated by two bacterial phyla; Firmicutes and Bacteroidetes, whereas phylum Betaproteobacteria was present only in non-rhizospheric bulk soil. Ex-situ (nursery growing condition) A. gerrardii resulted in restricted bacterial communities dominated by members of a single phylum, Bacteroidetes. Results indicated that the soil organic matter and rhizospheric environments might drive the bacterial community. Despite harsh climatic conditions, data demonstrated that A. gerrardii roots harbor endophytic bacterial populations. Our findings on bacterial community composition and structure have major significance for evaluating how Kuwait's extreme climatic conditions affect bacterial communities. The baseline data obtained in this study will be useful and assist in formulating strategies in ecological restoration programs including the application of inoculation technologies.